LITERATURE REVIEW: POLA KOMUNIKASI GURU DENGAN ORANG TUA DI SEKOLAH DASAR - Ayu Sulistyo, Desi; Rachmadyanti, Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Communication is a basic need that becomes an essential process in the exchange of thoughts, information, meanings, and feelings that allows for understanding and cooperation. In the context of education, communication between teachers and parents is an important aspect in improving the quality of education. Effective communication can facilitate the relationship between teachers and parents, as well as create a good learning environment. The purpose of this study is to explore the communication patterns of teachers with parents in elementary schools. This study uses a qualitative method of literature study. The source in this study is national articles in the last 10 years. The results of the study showed that communication can be done through direct personal/group communication, community programs, daily control books, WhatsApp groups, Coffee Morning programs, Guest Teacher programs, student portfolio media, Morning Tea programs, What We Will Learn programs and My Conference programs.These communications are able to improve the quality of student education. The findings of this literature review have implications for the importance of strengthening teacher-parent communication as part of efforts to improve the quality of education in elementary schools. Schools need to develop structured and sustainable communication, while parents as educational partners are expected to be more actively involved in communication.